Reasons as defaults - Horty, John Francis (New York : Oxford University Press, 2012)
In this volume, John Horty brings to bear his work in logic to present a framework that allows for answers to key questions about reasons and reasoning, namely: What are reasons, and how do they support actions or conclusions?
Includes bibliographical references.
Description based on print version record.
Keywords: Reason; Rationalism; Explanation; Justification (Theory of knowledge); Reasoning